Observed features of the water masses in the Halmahera Sea in November 2016 - Mochamad Riza Iskandar; Adi Purwandana; Dewi Surinati; Wang Zheng (Marine Science Department Diponegoro University, 2021)
Halmahera Sea is one of the locations in the eastern route of Indonesian Throughflow (ITF), where high salinity water is mainly transported by the ITF. The description of water mass in the Halmahera Sea from the perspective of water mass, and related mixing is important. It is not only useful for understanding water mass features, but it can also be used to determine the strength of the turbulent mixing, and so allow how it relates to the water transformation. Here, we report the water mass properties and estimation of mixing quantities in the Halmahera Sea from the CTD profiles based on recent onboard observations during the IOCAS cruise in November 2016. The water mass analysis was done by examining the characteristics of water types in the Temperature-Salinity (T-S) diagram. The mixing estimation uses the density profile derived from temperature and salinity profiles and the quantification of vertical turbulence observed by density overturn. Halmahera Sea is to be found as the location where the thermocline salinity changes abruptly, it is shown from the erosion of salinity maximum in the density of 22-26σθ decreased from the north to the south of the basin. It is associated with strong mixing with spots of higher vertical diffusivity in the thermocline and intermediate layer. In the upper layer, the mixed layer depth in the Halmahera Sea is relatively shallow with an average of about 16.95 m and it is associated with weak wind stress during this month.